1993
DOI: 10.1002/chin.199330185
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Activities of Meribendan and Related Heterocyclic Benzimidazolo‐pyridazinones.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…For example, the synthesis of 4-(5H-Imidazo[4,5-c]pyridazin-6-yl)-3-methoxy-thiobenzoic acid S-methyl ester from Benzene-1,2-diamine with positive inotropic activity on isolated paced guinea pig papillary muscle 5 . In addition, a study showed the preparation of meribendan (5-methyl-6[2-(3-pyrazolyl)-5-benzimidazoyl]-2,3,4,5-tetrahydro-pyridazin-3-one) through reaction of pyrazole-3-carboxaldehyde with cyanuric chloride and their positive inotropic activity using a guinea pig heart model 6 . Other study display the reaction of (3-phenylpyridin-2-yl)methylamine with dichloroacetaldehyde to form the compound methyl 3-methyl-8-phenylimidazo[1,5-a]pyridine-1-carboxylate; it is noteworthy that this compound produce positive inotropic activity in a papillary cat muscle model 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the synthesis of 4-(5H-Imidazo[4,5-c]pyridazin-6-yl)-3-methoxy-thiobenzoic acid S-methyl ester from Benzene-1,2-diamine with positive inotropic activity on isolated paced guinea pig papillary muscle 5 . In addition, a study showed the preparation of meribendan (5-methyl-6[2-(3-pyrazolyl)-5-benzimidazoyl]-2,3,4,5-tetrahydro-pyridazin-3-one) through reaction of pyrazole-3-carboxaldehyde with cyanuric chloride and their positive inotropic activity using a guinea pig heart model 6 . Other study display the reaction of (3-phenylpyridin-2-yl)methylamine with dichloroacetaldehyde to form the compound methyl 3-methyl-8-phenylimidazo[1,5-a]pyridine-1-carboxylate; it is noteworthy that this compound produce positive inotropic activity in a papillary cat muscle model 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, poly‐functionalized pyrroles as scaffolds show enormous significance in material science . Besides, they have been applied as anti‐inflammatory, antitumor, antioxidants, antibacterial and antifungal agents …”
Section: Introductionmentioning
confidence: 99%
“…In addition, polysubstituted pyrroles are molecular frameworks having immense importance in material science [5]. They have also been used as antioxidants, antibacterial, ionotropic, antitumor, anti‐inflammatory, and antifungal agents [6–11]. Moreover, they are a highly versatile class of intermediates in the synthesis of natural products and in heterocyclic chemistry [12].…”
Section: Introductionmentioning
confidence: 99%